2013
DOI: 10.1097/mcg.0b013e31826be328
|View full text |Cite
|
Sign up to set email alerts
|

The Severity of Histologic Liver Lesions Is Independent of Body Mass Index in Patients With Nonalcoholic Fatty Liver Disease

Abstract: Approximately 1 of 8 NAFLD patients coming to a Greek tertiary liver center has normal BMI. On liver biopsy, normal BMI patients often have nonalcoholic steatohepatitis and histologic liver lesions of similar severity to the overweight or obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 53 publications
1
41
0
2
Order By: Relevance
“…Also, a significant percentage of patients (about 25%) had normal weight confirming that, even if positive energy balance and increased BMI substantially increase the risk of NAFLD, this latter may develop in individuals with normal BMI as well[41] e.g ., as a consequence of an uncorrected lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a significant percentage of patients (about 25%) had normal weight confirming that, even if positive energy balance and increased BMI substantially increase the risk of NAFLD, this latter may develop in individuals with normal BMI as well[41] e.g ., as a consequence of an uncorrected lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…[8] The prevalence of CD among patients with NAFLD has been reported as 2.2-7.9%[29, 30] and among these patients BMI was often in the normal range. [29] Conversely, little is known of the risks of NAFLD in those already diagnosed with CD.…”
Section: Discussionmentioning
confidence: 99%
“…[8] A high-fat diet and sedentary lifestyle are alterable risks, modifications here can yield improvements in NAFLD [9], and recovery after weight loss may be related to reduced insulin resistance. [10] Many adults and children with CD are overweight or obese at diagnosis, or become overweight after treatment [11, 12], increasing risks for NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic β‐cell dysfunction preceded glucose intolerance in patients with NASH but without obesity ( n = 20) compared to both insulin‐sensitive ( n = 30) and ‐insensitive ( n = 15) controls (matched for age, sex, and BMI) and could contribute to the development of type 2 diabetes in these patients . From a metabolic point of view, several studies reported that NALFD without obesity may be comparable with NAFLD with obesity (Table ) ( , ). In contrast, other authors have found the metabolic profile of NAFLD without obesity to be less severe when compared with NAFLD with obesity .…”
Section: Nafld and Its Comorbiditiesmentioning
confidence: 99%